Edaravone Attenuated Particulate Matter-Induced Lung Inflammation by Inhibiting ROS-NF-κB Signaling Pathway. (23rd April 2022) - Zeng, Yingying; Zhu, Guiping; Zhu, Mengchan; Song, Juan; Cai, Hui; Song, Yuanlin; Wang, Jian; Jin, Meiling
Abstract : Background . Particulate matter (PM) exposure is related to mitochondria dysfunction and airway inflammation. Antioxidant drug edaravone (EDA) is reported to improve the occurrence and development of oxidative stress-related diseases. At present, there is no data on whether EDA can alleviate lung inflammation caused by PM. Methods . The anti-inflammatory effects of EDA were investigated in urban PM-induced human bronchial epithelial cells (HBECs) and C57/BL6J mouse models. In vitro, its effects on the production of intracellular reactive oxygen species (ROS), mitochondrial membrane potential (MMP), and inflammatory cytokines were assessed by DCFH-DA staining, JC-1 assay, and real-time PCR, respectively. In vivo, the oxidant stress in lung tissues was assessed by dihydroethidium (DHE) staining and malondialdehyde (MDA) activity, and inflammatory cytokines in bronchoalveolar lavage fluid (BALF) were assessed by ELISA, respectively. Furthermore, the potential signaling pathways were studied by siRNA transfection and western blot. Results . PM increased the expression of inflammatory cytokines and protein, including IL-6, IL-1 α, IL-1 β, and COX-2, while these alternations were significantly alleviated following EDA treatment in a dose-dependent manner. EDA treatment also alleviated the inflammatory responses in lung tissues of PM-exposed mice. We further showed mitochondrial dysfunction in PM-exposed HBECs and mice, which were reversed by EDA treatment. Moreover, the phosphorylation of NF- κ B p65 in PM-exposed HBECs and mice was weakened by EDA. Transfection with NF- κ B p65 siRNA further inhibited PM-induced inflammation in HBECs. Conclusion . We demonstrated that EDA treatment had a protective role in PM-induced lung inflammation through maintaining mitochondrial balance and regulating the ROS-NF- κ B p65 signaling pathway. This provided a new therapeutic method for PM-induced lung inflammation in the future.